Relationship between external weather conditions and number of hibernating bats in two caves in the western Italian Alps - Toffoli, Roberto (European Journal of Ecology, 2021)
Weather conditions can influence the hibernation behaviour of temperate cave-dwelling bats that are tolerant to low temperatures, and their number can be correlated with weather variables. In this work a first assessment on the correlation between the number of individuals of three species of hibernating bats (Barbastella barbastellus, Myotis emarginatus and Rhinolophus hipposideros) and the environmental weather conditions before the survey was carried out is provided for two hibernacula of the Italian Western Alps.For the B. barbastellus, a significant inverse correlation was observed between the number of bats detected and the average daily temperature for thirty days preceding the count (p= 0.036) and ten days before counting (p= 0.036). A significant positive correlation was observed for M. emarginatus between the number of individuals and the average daily temperatures for thirty days preceding the count (p= 0.018). For R. hipposideros, a significant inverse correlation was observed with the average daily temperatures for the ten days before the count (p= 0.048) and the differences in the maximum and minimum temperature of the ten days preceding the count (p= 0.002).Results of this study show how the ambient temperatures before a count can influence the number of bats present in hibernacula. This confirms how the abundance of bats at underground hibernating sites can be used as an indicator of climate change, as temperature is an important factor controlling hibernation, although  further studies are needed in order to better evaluate how the climatic variables interact with each other in regulating the number of bats in the hibernacula.